Cohort study on maternal cytomegalovirus seroprevalence and prevalence and clinical manifestations of congenital infection in China. Issue 5 (February 2017) - Wang, Shiwen; Wang, Tongzhan; Zhang, Wenqiang; Liu, Xiaolin; Wang, Xiaofang; Wang, Haiyan; He, Xiaozhou; Zhang, Shunxian; Xu, Shuhui; Yu, Yang; Jia, Xingbing; Wang, Maolin; et al.
Abstract : Abstract: Congenital cytomegalovirus (CMV) infection is the leading viral cause of birth defects and developmental disabilities in developed countries. However, CMV seroprevalence and burden of congenital CMV infection are not well defined in China. Cohort of newborns from 5 birthing hospitals in 2 counties of Shandong Province, China, were enrolled from March 2011 to August 2013. Dried blood spots (DBS) and saliva were collected within 4 days after birth for IgG testing for maternal seroprevalence and real-time PCR testing for congenital CMV infection, respectively. Among 5020 newborns tested for CMV IgG, 4827 were seropositive, resulting in CMV maternal seroprevalence of 96.2% (95% confidence interval [CI]:95.6%–96.7%). Of the 10, 933 newborns screened for congenital CMV infection, 75 had CMV detected, resulting in an overall prevalence of 0.7% (95% CI: 0.5%–0.9%), with prevalences of 0.4% (14/3995), 0.6% (66/10, 857), and 0.7% (52/7761) for DBS, wet saliva, and dried saliva specimens screened, respectively. Prevalence of congenital CMV infection decreased with increasing maternal age (0.9%, 0.6%, and 0.3% among newborns delivered from mothers aged 16–25, 26–35, and >35 years, respectively; P  = 0.03), and was higher among preterm infants than full term infants (1.3% vs 0.6%, P  = 0.04), infants with intrauterine growth restriction (IUGR) than those without (1.8% vs 0.7%, P  = 0.03), and twins or triplets than singleton pregnancies (2.8% vs 0.7%, P  = 0.04). None of the 75 newborns exhibited symptomatic congenital CMV infection, and there was no difference in clinical characteristics and newborn hearing screening results between infants with and without congenital CMV infection at birth. Congenital CMV infection prevalence was lower and the clinical manifestations were milder in this relatively developed region of China compared to populations from other countries with similarly high maternal seroprevalence. Follow-up on children with congenital CMV infection will clarify the burden of disabilities from congenital CMV infection in China.